2023
DOI: 10.1002/eji.202350559
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional cytokine production marks influenza A virus‐specific CD4 T cells with high expression of survival molecules

Abstract: Cytokine production by memory T cells is a key mechanism of T cell mediated protection. However, we have limited understanding of the persistence of cytokine producing T cells during memory cell maintenance and secondary responses. We interrogated antigen‐specific CD4 T cells using a mouse influenza A virus infection model. Although CD4 T cells detected using MHCII tetramers declined in lymphoid and non‐lymphoid organs, we found similar numbers of cytokine+ CD4 T cells at days 9 and 30 in the lymphoid organs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…To investigate the consequences of the anti-MHCII treatment, we used flow cytometry to identify IAV-specific CD4 T cells that recognise the immunodominant nucleoprotein (NP) peptide, 311-325, or by gating on EYFP+ CD4 T cells in infected TRACE mice, Figure 5A-B and gating in Supplementary Figure 5. Our prior study demonstrated similar kinetics and differentiation into cytokine producing cells between CD4 T cells identified via these two methods 29 .…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…To investigate the consequences of the anti-MHCII treatment, we used flow cytometry to identify IAV-specific CD4 T cells that recognise the immunodominant nucleoprotein (NP) peptide, 311-325, or by gating on EYFP+ CD4 T cells in infected TRACE mice, Figure 5A-B and gating in Supplementary Figure 5. Our prior study demonstrated similar kinetics and differentiation into cytokine producing cells between CD4 T cells identified via these two methods 29 .…”
Section: Resultsmentioning
confidence: 75%
“…To first provide an overview of the lung immune response, we combined precision cut lung slices (PCLS) with tissue clearing and confocal microscopy. To enable us to identify IAV-specific CD4 T cells, we took advantage of a reporter mouse, TRACE, that we have developed and previously characterised 28, 29 . Activated T cells in these triple transgenic mice express rtTA under the control of part of the interleukin 2 promoter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations